Socio-economic perspectives on consumer engagement and buying behavior - Kaufmann, Hans Ruediger 1958-; Panni, Mohammad Fateh Ali Khan 1981- (Business Science Reference, 2017)
"This book provides some insights on new dimensions and emerging contexts on the socioeconomic perspectives on the consumer engagement and behavior and marketing 4.0, consumer information system, surveillance in service encounters, e-commerce. This book demonstrates fundamental concepts on consumerism, consumer boycotts or activism, customer satisfaction and consumption of green products"-- Provided by publisher.